Postbiotics from Lactobacillus delbrueckii Alleviate Intestinal Inflammation by Promoting the Expansion of Intestinal Stem Cells in S. Typhimurium-Induced Mice - Mengting Wang; Yuting Ren; Xin Guo; Yanxin Ye; Haining Zhu; Jiaqi Zhang; Zan Huang; Kaifan Yu (Foods, 2024)
Previous studies have demonstrated that L. delbrueckii plays beneficial roles in modulating the gut microbiota, enhancing the intestinal barrier, and promoting animal growth. Postbiotics have a similar or even superior effect in protecting intestinal health compared to probiotics due to their excellent stability, extended shelf life, and safety. However, the protective effects and underlying mechanism of postbiotics from L. delbrueckii in intestinal inflammation remain unclear. In this study, we demonstrated the beneficial impact of postbiotics from L. delbrueckii on intestinal health by establishing a S. Typhimurium-induced intestinal inflammation model in mice, which included inactivated bacteria and supernatant. The results revealed that the probiotics and postbiotics from L. delbrueckii increased the survival rate and body weight of S. Typhimurium-induced mice, increased the level of IL-10, and decreased the levels of TNF-α and IL-6, thereby alleviating intestinal inflammation. Meanwhile, treatment with postbiotics decreased the levels of D-LA, DAO, and LPS and promoted the expression of Occludin, ZO-1, and Claudin-1 in the serum and jejunum, suggesting an improvement in intestinal barrier function by postbiotics. Additionally, the postbiotics modulated gut microbial diversity, increased the ratio of Firmicutes and Bacteroidetes, and restored the abundance of Muribaculaceae, Lachnospiraceae_NK4a136_groups, and Alloprevotella in S. Typhimurium-infected mice. Moreover, postbiotics from L. delbrueckii promoted the expansion of intestinal stem cells (ISCs) and increased the numbers of Paneth and Goblet cells. Taken together, these data revealed the beneficial role of postbiotics from L. delbrueckii in protecting against intestinal inflammation by promoting the expansion of ISCs.